Increasing body mass index and abdominal subcutaneous fat thickness are associated with increased skin-to-epidural space distance in pregnant women. (May 2019) - Eley, V.A.; Chin, A.; Sekar, R.; Donovan, T.; Krepska, A.; Lawrence, M.; Bell, S.; Ralfe, K.; McGrath, S.; Webb, L.; Robinson, A.; van Zundert, A.; et al.
Highlights: Abdominal subcutaneous fat thickness (SCFT) is a measure of central adiposity. Abdominal SCFT is correlated with body mass index. Body mass index is more strongly related to skin-to-epidural space distance. Further work will evaluate if SCFT predicts difficulty locating the epidural space. Abstract: Background: Body mass index does not indicate the distribution of adipose tissue. Central adiposity may be measured using ultrasound measurement of subcutaneous fat thickness. This study determined if the abdominal subcutaneous fat thickness measured correlated with skin-to-epidural space distance at delivery, and compared this with the booking body mass index. Methods: We analysed a sub-set of participants from a single-centre, prospective cohort study that assessed the relationship between subcutaneous fat thickness and maternity outcomes. Abdominal subcutaneous fat thickness measurements were obtained during the routine fetal anomaly scan. The skin-to-epidural space distance was obtained in those having epidural or combined spinal-epidural analgesia. Linear regression was used to test for strength of association and adjusted R 2 values calculated to determine if subcutaneous fat thickness or body mass index was more strongly associated with skin-to-epidural space distance. Results: The 463 women had a median (IQR) booking body mass index of 25.0 kg/m 2 (21.8–29.3) and subcutaneous fat thickness of 16.2 mm (13.0–21.0). The median (IQR) skin-to-epidural space distance was 5.0 cm (4.5–6.0). Both parameters significantly correlated with skin-to-epidural space distance ( r =0.53 and 0.68 respectively, P  <0.001). Adjusted linear regression coefficient (95% CI) for subcutaneous fat thickness was 0.09 (0.08 to 0.11), R 2 =0.30 and for body mass index 0.12 (0.11 to 0.13), R 2 =0.47. Conclusions: Booking body mass index had a stronger relationship with skin-to- epidural space distance at delivery than subcutaneous fat thickness, explaining 47% of the variation in the skin-to-epidural distance.